2017
DOI: 10.1136/heartjnl-2016-310986
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of resting heart rate and association with mortality in middle-aged and elderly twins

Abstract: Objective Resting heart rate (RHR) possibly has a hereditary component and is associated with longevity. We used the classical biometric twin study design to investigate the heritability of RHR in a population of middle-aged and elderly twins and, furthermore, studied the association between RHR and mortality. Methods In total, 4282 twins without cardiovascular disease were included from the Danish Twin Registry, hereof 1233 twin pairs and 1816 ’single twins’ (twins with a non-participating co-twin); mean ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 30 publications
2
11
1
Order By: Relevance
“…46 In the elderly population, elevated heart rate is also an independent risk factor for shortterm 47 and long-term mortality. 48 This phenomenon fits well with the Levine theory that subjects with higher heart rate are dying at an earlier age because of the depletion of their heart rate capital. 49 Elevated heart rate may reflect cardiovascular autonomic nervous dysfunction and decreased cardiopulmonary function.…”
Section: Associated Risk Factors Of Frailtysupporting
confidence: 83%
“…46 In the elderly population, elevated heart rate is also an independent risk factor for shortterm 47 and long-term mortality. 48 This phenomenon fits well with the Levine theory that subjects with higher heart rate are dying at an earlier age because of the depletion of their heart rate capital. 49 Elevated heart rate may reflect cardiovascular autonomic nervous dysfunction and decreased cardiopulmonary function.…”
Section: Associated Risk Factors Of Frailtysupporting
confidence: 83%
“…Namely, several recent studies showed that RHR is a trait with a genetic influence in subjects free of cardiovascular disease. 12,13 Hoed et al 14 showed that difference in approximately 10 bpm in RHR could be explained with specific associations to gene loci.…”
Section: Introductionmentioning
confidence: 99%
“…In the Systolic Heart failure treatment with the If inhibitor ivabradine (SHIFT) trial the addition of ivabradine to standard treatment in chronic cardiac failure with reduced ejection fraction led to a significant reduction in the primary endpoints of hospitalisations for treatment and death 7. Jensen et al 8 discuss whether we should define a high heart rate and then focus on lifestyle modifications to reduce cardiovascular risk factors. For example, a graded exercise programme can result in a reduction of RHR.…”
mentioning
confidence: 99%